The Computers And Radio Broadcasters’ Politeness - Wiwik Yulianti; Fx Sawardi; Henry Yustanto; Bakdal Ginanjar; Chattri Sigit Widyastuti; Hanifullah Syukri (Postgraduate, University of Mataram, 2023)
With the technological advances of the 21st century, radio broadcasting has become more dependent on computers than ever before. Computers are used in radio broadcasting for a number of different tasks, including automation, control, monitoring, and logging. Automation is the most common use of computers in radio broadcasting. Automation software is used to control the playback of music and other audio content. This allows radio stations to operate without a live DJ or presenter. But in this case the presenter still needs to deliver the talk show program. The article studies the radio broadcasters’ language politeness, as part of the strategies in attracting the listeners. It aims to reveal the politeness principles used during the conversations of the radio programs. It deployed a Content Analysis combined with recording technique for the data collecting technique. Meanwhile, the analysis applied a Pragmatics Matching method through a Contextual Approach. The finding revealed the speaker’s compliance and violation of the politeness principles.